2018
DOI: 10.1002/ijc.31319
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of nutrients involved in one‐carbon metabolism and risk of urothelial cell carcinoma: A prospective cohort study

Abstract: Nutrients involved in one-carbon metabolism may play a role in carcinogenesis through DNA replication, repair and methylation mechanisms. Most studies on urothelial cell carcinoma (UCC) have focused on folate. We sought to examine the association between B-group vitamins and methionine intake and UCC risk, overall and by subtype, and to test whether these associations are different for population subgroups whose nutritional status may be compromised. We followed participants in the Melbourne Collaborative Coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
2
8
2
Order By: Relevance
“…Dietary studies from the MCCS have examined associations between B vitamin intakes and risk for several cancers but have only found inconsistent or weak associations. We also found no association between dietary intakes of B vitamins and UCC in our prospective cohort . These findings are in contrast to a large Spanish case–control study which reported protective associations with bladder cancer risk for B2, B6, B9 and B12 intakes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Dietary studies from the MCCS have examined associations between B vitamin intakes and risk for several cancers but have only found inconsistent or weak associations. We also found no association between dietary intakes of B vitamins and UCC in our prospective cohort . These findings are in contrast to a large Spanish case–control study which reported protective associations with bladder cancer risk for B2, B6, B9 and B12 intakes.…”
Section: Discussioncontrasting
confidence: 99%
“…We also found no association between dietary intakes of B vitamins and UCC in our prospective cohort. 17 These findings are in contrast to a large Spanish case-control study 14 which reported protective associations with bladder cancer risk for B2, B6, B9 and B12 intakes. Risk of recall bias and reverse causation are a potential limitation of retrospective casecontrol studies.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…A meta‐analysis observed an inverse association between folate intake and bladder cancer risk in six case–control studies (OR = 0.73; 95% CI 0.57–0.89), but not in seven cohort studies (relative risk = 0.96; 95% CI 0.81–1.10) (3). Also a recent cohort study found no association of dietary intake of folate and other B‐group vitamins with UCC risk, and did not observe heterogeneity across UCC subtypes . Self‐reported dietary folate intake may be a less accurate measure of folate status than blood folate concentrations, which reflect both dietary and supplemental intakes and is directly related to bioavailability.…”
Section: Discussionmentioning
confidence: 96%